2020
DOI: 10.19183/how.27.2.566
|View full text |Cite
|
Sign up to set email alerts
|

Inquiring into the Coloniality of Knowledge, Power, and Being in EFL Textbooks

Abstract: This article inquires into the coloniality present in EFL textbooks, which continue being used as the core resource for language learning and teaching in Colombia. However, its instrumentalization, imperialism, and exploitation as an instrument of subalternation suggest that EFL textbooks produced by foreign and local publishing houses in the Colombian context are colonised in three interrelated dimensions: knowledge, power, and being. Therefore, this research proposal aims at unveiling the ontological, episte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Doing research on critical interculturality can pose a challenge because although researchers might be willing to embrace decolonial theories, they are forced to re-think their positionality towards new ways of being, knowing, and power. Despite this, Critical Interculturality (CI) is being studied by different scholars (Granados-Beltrán, 2018a, 2018bNúñez-Pardo, 2020a, 2020bRamos-Holguín, 2013. For example, Granados-Beltrán (2018a, 2018b) has indicated that CI, from a decolonial standpoint, "can support initial foreign language teacher education ontologically and epistemologically" (Granados-Beltrán, 2018b, p. 10).…”
Section: Critical Interculturality In Elt Colombian Scholarshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Doing research on critical interculturality can pose a challenge because although researchers might be willing to embrace decolonial theories, they are forced to re-think their positionality towards new ways of being, knowing, and power. Despite this, Critical Interculturality (CI) is being studied by different scholars (Granados-Beltrán, 2018a, 2018bNúñez-Pardo, 2020a, 2020bRamos-Holguín, 2013. For example, Granados-Beltrán (2018a, 2018b) has indicated that CI, from a decolonial standpoint, "can support initial foreign language teacher education ontologically and epistemologically" (Granados-Beltrán, 2018b, p. 10).…”
Section: Critical Interculturality In Elt Colombian Scholarshipmentioning
confidence: 99%
“…In Colombia, the field of FLT and learning is also beginning to embrace a critical intercultural perspective. Some Colombian ELT scholars (Álvarez Valencia, 2014;García & García, 2014;Granados-Beltrán, 2016, 2018a, 2018bNúñez-Pardo, 2020a, 2020bUsma Wilches et al, 2018) have addressed critical intercultural discourses depending on their interests and the context in which these issues take place. Theoretical knowledge and studies regarding CI have been a relevant and necessary initial development; however, it seems the teaching and learning practices of pedagogical experiences from a critical intercultural perspective remain at an early stage.…”
Section: Introductionmentioning
confidence: 99%
“…English language teaching (ELT) and teacher education (TE) have not escaped this hegemony, causing an unquestionable dominance of the inner-circle countries (Kachru, 1990) regarding initial teacher education. In Colombia, for example, scholars are interested in decolonizing materials (Núñez-Pardo, 2020, English language pedagogy (Ubaque-Casallas, 2021), higher education from the perspective of indigenous students (Usma et al, 2018), and doctoral TE (Castañeda-Peña & Méndez-Rivera, 2022); some even have concentrated on exploring the racialization of the ELT field (Bonilla Medina & Finardi, 2022). However, studies that question, challenge, or attempt to document racist practices in ELT and TE are scarce.…”
Section: Introductionmentioning
confidence: 99%